New architecture of a petal-shaped Nb2O5 nanosheet film on FTO glass for high photocatalytic activity. Issue 12 (25th January 2016) - Liu, Xiaobin; Que, Wenxiu; Xing, Yonglei; Yang, Yawei; Yin, Xingtian; Shao, Jinyou
Abstract : A petal-shaped Nb2 O5 nanosheet thin film was grown directly on FTO glass substrate via a facile hydrothermal method. The petal-shaped Nb2 O5 nanosheet array film without annealing showed excellent photocatalytic activity for degrading aqueous rhodamine B. Abstract : A petal-shaped Nb2 O5 nanosheet thin film was grown directly on a transparent conductive fluorine-doped tin oxide (FTO) glass substrate via a facile hydrothermal method. Structural and morphological characterization showed that the Nb2 O5 nanosheets with a thickness of about 30 nm stood almost vertically on the FTO glass substrate. The vertical thickness of the petal-shaped Nb2 O5 nanosheet array film, which grows along (020) and (003) crystal planes, was 2–3 μm. The petal-shaped Nb2 O5 nanosheet array film on FTO glass without annealing showed excellent photocatalytic activity for degrading aqueous rhodamine B. The activity was better than that of the porous P25 film with a thickness of 50 μm. The new architecture is suitable for reuse in photocatalytic applications.